Retaining the epigastric trocar, until rest all ports closed decreases post-operative shoulder pain in laparoscopic cholecystectomy patients - Leesa Misra; Navya Teja; Mishra, Swastik; Manash Ranjan Sahoo (Asian Journal of Medical Sciences, 2023)
Background: Laparoscopic cholecystectomy has become the mainstay of treatment for gallstone disease cases due to its lower morbidity and pain compared to open techniques. Unfortunately, the use of carbon dioxide to insufflate the abdomen is the main contributor to post-operative shoulder pain. Aims and Objectives: The aim of the study was to evaluate the effectiveness of retaining the epigastric port trocar in position until rest all ports closed after completion of lap cholecystectomy in decreasing the post-operative shoulder pain. Materials and Methods: A prospective, randomized, and clinical trial was done in AIIMS hospital, Bhubaneswar, on 102 patients who have undergone laparoscopic cholecystectomy. The patients were alternatively selected, one in the study group (52) and the other in the control group (50). For those patients in the study group, after the completion of the surgery, the epigastric port trocar is retained in position until the rest of all ports were closed. In the control group, all trocars were removed and port closure was done. The patients were evaluated for the next 24 h for post-operative shoulder pain. A numerical rating scale (NRS) was used to assess shoulder pain on patient arrival to the ward, at 4, 6, 12, and 24 h postoperatively. One hundred and two patients were included in the final data analysis. Results: NRS pain scores were significantly lower in the study group at 6, 12, and 24 h post-laparoscopic cholecystectomy compared to the control group with no additional requirement of IV analgesics. Conclusion: Retaining the epigastric trocar in position is an easy way that is beneficial in reducing post-operative shoulder pain post laparoscopic cholecystectomy surgery.